Optimized design of a hyperflexible sieve electrode to enhance neurovascular regeneration for a peripheral neural interface. (August 2021) - Veith, Austin; Li, Xue; Modi, Hailey; Abbaspour, Ali; Luan, Lan; Xie, Chong; Baker, Aaron B.
Abstract: One in 190 Americans is currently living with the loss of a limb resulted from injury, amputation, or neurodegenerative disease. Advanced neuroprosthetic devices combine peripheral neural interfaces with sophisticated prosthetics and hold great potential for the rehabilitation of impaired motor and sensory functions. While robotic prosthetics have advanced very rapidly, peripheral neural interfaces have long been limited by the capability of interfacing with the peripheral nervous system. In this work, we developed a hyperflexible regenerative sieve electrode to serve as a peripheral neural interface. We examined tissue neurovascular integration through this novel device. We demonstrated that we could enhance the neurovascular invasion through the device with directional growth factor delivery. Furthermore, we demonstrated that we could reduce the tissue reaction to the device often seen in peripheral neural interfaces. Finally, we show that we can create a stable tissue device interface in a long-term implantation that does not impede the normal regenerative processes of the nerve. Our study developed an optimal platform for the continued development of hyperflexible sieve electrode peripheral neural interfaces. Graphical abstract: Image 1